Building of Pressure-Assisted Ultra-High Temperature System and Its Inactivation of Bacterial Spores - Liang, Dong; Zhang, Liang; Wang, Xu; Wang, Pan; Liao, Xiaojun; Wu, Xiaomeng; Chen, Fang; Hu, Xiaosong (Frontiers in Microbiology, 2019)
The pressure-assisted ultra-high temperature (PAUHT) system was built by using soybean oil as pressure-transmitting medium, and the multiple regression equation of soybean oil temperature change (ΔT_P) during pressurization as a function of initial temperature (Ti) and set pressure (P) was developed: ΔT_P= -13.45 + 0.46〖 T〗_i + 0.0799 P – 0.0037 T_i^2 – 2.83 ×〖 10〗^(-5) P^2. The fitted model indicated that the temperature of the system would achieve ≥ 121 ºC at 600 MPa when the initial temperature of soybean oil was ≥ 84 ºC. The PAUHT system could effectively inactivate spores of Bacillus subtilis 168 and Clostridium sporogenes PA3679 (less than one min). Treatment of 600 MPa and 121 ºC with no holding time resulted in a 6.75 log reductions of B. subtilis 168 spores, while treatment of 700 MPa and 121 ºC with pressure holding time of 20 s achieved more than 5 log reductions of C. sporogenes PA3679 spores. By comparing the PAUHT treatment with high pressure or thermal treatment alone, and also studying the effect of compression on spore inactivation during PAUHT treatment, the inactivation mechanism was further discussed and could be concluded as follows: both B. subtilis 168 and C. sporogenes PA3679 spores were triggered to germinate firstly by high pressure, which was enhanced by increased temperature, then the germinated spores were inactivated by heat.